2019
DOI: 10.1002/jac5.1158
|View full text |Cite
|
Sign up to set email alerts
|

Improving hypertension control through a collaboration between an academic medical center and a chain community pharmacy

Abstract: Introduction Approximately one‐third of adults in the United States have hypertension (HTN), leading to increased morbidity and mortality. Objectives This quality improvement intervention was designed to improve HTN control among community‐dwelling adults through collaboration between patient‐centered medical homes (PCMH) within an academic medical center and chain community pharmacies. Methods Four PCMH sites in Ann Arbor, Michigan that were in close proximity to two Meijer pharmacies participated in this stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 21 publications
1
8
0
Order By: Relevance
“…The outcomes that were assessed in this study were QoL, adherence to medication management and cost of medications. Clinical outcome of hypertension management (blood pressure changes) was not assessed in this study because of the abundance of studies that concentrated on the impact of interventions on the same 3,18,20,21,23 . The intervention was carried out for 6 months, as was done in similar studies despite the disease states being chronic conditions 31,32 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The outcomes that were assessed in this study were QoL, adherence to medication management and cost of medications. Clinical outcome of hypertension management (blood pressure changes) was not assessed in this study because of the abundance of studies that concentrated on the impact of interventions on the same 3,18,20,21,23 . The intervention was carried out for 6 months, as was done in similar studies despite the disease states being chronic conditions 31,32 …”
Section: Discussionmentioning
confidence: 99%
“…22 The finding of the study was also similar to another conducted in Michigan, as the product of a collaboration between an academic medical centre and chain community pharmacy. 23 The aforementioned studies and others in the literature were majorly conducted in developed countries where healthcare service is at advanced state. Hence, there is a need to justify the possibility of community pharmacists involvement in the management of a chronic disease like hypertension in the low-and middle-income countries.…”
Section: Introductionmentioning
confidence: 99%
“…Further evaluation of this program is underway in collaboration with the Centers for Disease Control and Prevention to address some of these limitations. 31…”
Section: Discussionmentioning
confidence: 99%
“…A considerable body of literature exists documenting the variety of approaches that have been evaluated to improve management of chronic disease, often called chronic care management (CCM) . Studies have demonstrated that pharmacists, including community pharmacists, can make valuable contributions to multidisciplinary CCM teams …”
Section: Introductionmentioning
confidence: 99%